Quality Analysis of Swarnadira Gown with Songket Fabric Application on the Bustier Section - Semi Anyiarizki Wiji Pangesti; Widowati Widowati (Jurnal Penelitian Pendidikan, 2026)
This study aims to design and analyze the quality of the evening gown “Swarnadira” through the application of songket fabric on the bustier as the main design element. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The design process was carried out through literature studies, concept development, moodboard creation, and product realization using a mermaid silhouette and decorative bead details. Product quality assessment was conducted using the expert judgment method involving expert and trained panelists based on aspects of design, size, aesthetics, sewing techniques, piece performance, and product uniqueness. The results showed that the “Swarnadira” evening gown achieved a very good quality category in most indicators, while the sewing technique aspect obtained a good quality category. These findings indicate that the piece has good quality in terms of aesthetics, function, and comfort. Therefore, the application of songket fabric on the bustier is able to enhance aesthetic value while strengthening cultural identity in modern evening gown design.